Reversible immobilization of engineered molecules by Ni-NTA chelators - Maly, J; Di Meo, C; De Francesco, M; Masci, A; Masojidek, J; Sugiura, M; Volpe, A; Pilloton, R (Bioelectrochemistry (Amsterdam, Netherlands), 2004)
Electrochemical synthesis of nickel-nitrilotriacetic acid (Ni-NTA) chelators, for subsequent immobilization of (His)(6)-tagged proteins (Photosystem II (PSII) as model molecule), on Au or Au-graphite electrodes is compared to chemical synthesis. Results show: (i) higher Ni-NTA surface density, (ii) shorter treatment time (1-12 min vs. 16 h normally needed for self-assembled monolayer (SAM)), (iii) possibility of addressing the chelator to only one Au electrode, in a sensor micro-array.
Keywords: biokompatibilní potahované materiály; Electrodes; Photosystem II Protein Complex; Electrochemistry; elektrochemie; světlo; Protein Engineering; Biosensing Techniques; elektrody; Recombinant Proteins; Organometallic Compounds; biosenzitivní techniky; Light; organokovové sloučeniny; kyselina nitrilotrioctová; Coated Materials, Biocompatible; fotosystém II (proteinový komplex); rekombinantní proteiny; Adsorption; proteinové inženýrství; chelátory; Nitrilotriacetic Acid; adsorpce; Chelating Agents